Joint caching and communication for future wireless networks - Amer, Ramy (Trinity College Dublin. School of Engineering. Discipline of Electronic & Elect. Engineering, 2021)
Recently, caching the most popular content at network edges has emerged as a promising technique to avoid serving all requests from the core network through highly congested backhaul links. From the caching perspective, there are multiple types of network architectures, namely, caching on femtocells in small cell networks, caching on remote-radio-head (RRH) in cloud-radio-access-networks (CRANs), caching for mobile devices, and caching for unmanned aerial vehicle (UAV) networks. This thesis conducts a comprehensive study, analysis, and optimization of the problem of content caching on terrestrial mobile devices in various works, as well as aerial users (i.e., UAV-user equipments (UAV-UEs)). In particular, in the first part of this thesis, we study the joint caching and communication problem for cache-enabled device-to-device (D2D) network. Key performance indicators such as offloading gain, throughput, average delay, energy consumption, and spectral efficiency are then characterized and optimized. For instance,We propose a novel D2D collaborative caching architecture, where popular files are cached in the users’ surplus memory and then shared with others, either neighboring users in the same proximity or remote users in the same cell (denoted as cooperation). We show that allowing such content sharing helps reduce the network average delay per request. We also investigate the average per-request throughput for different caching schemes and conducted the scaling analysis for the average sum throughput. We then proposed a joint communication and caching optimization framework for clustered D2D networks. Joint channel access and probabilistic caching for optimizing the offloading gain and energy consumption is first conducted. We then proposed a novel joint bandwidth partitioning and caching scheme to minimize the average delay per content request. Furthermore, we extended our work to study and optimize probabilistic caching for clustered D2D caching networks whose devices undergoing coordinated multipoint (CoMP) transmissions. In the second part of the thesis, we turn our attention to a new wireless network architecture where ground base stations (BSs) deliver content and provide coverage to contemporary aerial users. We first propose a content delivery network for co-existing ground and UAV-UE.We particularly investigate the use of beamforming for simultaneous content delivery to an aerial user co-existing with multiple ground users. We then study the performance of aerial users under three-dimensional (3D) practical antenna configurations. We consider both static and mobile aerial users and characterize their performance. Finally, we investigate the use CoMP transmission along with caching to provide seamless connectivity to aerial users. We consider a network of clustered cache-enabled small BSs (SBSs) serving aerial users where requested content is cooperatively transmitted from collaborative ground SBSs. Scenarios with static and mobile aerial users are also considered.
Keywords: wireless networks; caching; mobile devices; unmanned aerial vehicles